Menstrual Health: How Aware and healthy young girls are? - Sharma , Priyanka (International Journal of Psychosocial Rehabilitation, 2013)
Background: Menstruation is a normal physiological process occurring every month throughout the reproductive age of females. Menstruation is still considered as something shameful and young girls face self-imposed and external restrictions during mensural cycle. The school going girls still lack knowledge regarding menstruation, menstrual hygiene, reproduction, and dietary knowledge as well. The objective of this study is to see the awareness level regarding menstruation amongst adolescent girls of Jammu region. An attempt is also made to find the association between knowledge regarding menstruation and depression level amongst urban and rural adolescent girls of Jammu. Method: The study was conducted in four schools in which 106 girls participated. Girls were to complete questionnaire concerning demographic characteristics, menstruation practices detailing, depression, anxiety and stress scale consisting of 21 questions (DASS-21). Girls voluntarily agreed to answer questionnaire under the supervision of researcher. The data was then analyzed and conclusions were drawn regarding mensural practices amongst the girls. Results: Mean age of the sampled girls was 10.6 years. Mean age at menarche was 7.6 years. 53.77% girls did not have adequate knowledge about menstruation and for 71.69% girls first informant about menstruation was the mother. 75.47 % girls did not have adequate knowledge about the menstrual hygiene. 57.55% girls felt that pain during menstruation.34.90 % girls were reported missing school during menstruation. About 58.49% of the subjects had stress, 77.36% had depression and 78.30% had anxiety during mensural cycle. Conclusion: The knowledge regarding menstruation was found to be inadequate among majority of the adolescent girls, however whatever knowledge girls had about mensuration their major source was mothers. Over 80% girls are disposing of sanitary napkins in dustbin or open which may turn out to be hazardous. Menstruation also contributes to absenteeism among school girls in Jammu region. Girls are missing school because of poor product supply, water and sanitation facilities and a lack of pain management. Strengthening of MHM programme in Jammu is needed. Education on awareness, access to hygienic absorbent and disposal of MHM items need to be addressed